Synthesizing of SnS2 photocatalyst from SnO2 powders by thermal sulfurization with varying temperature (400 °C and 500 °C) and time - OK, ALAADDİN CEM; SARIOĞLU, CEVAT (My University, 2023)
SnS2 from SnO2 powders was successfully produced by the thermal sulfurization method to obtain pure SnS2 powders by varying the sulfurization temperature and time. XRD analysis confirmed pure hexagonal SnS2 powders at 400 and 500 °C after 24 h of sulfurization. Grain size analysis in SEM indicated that the average grain size of powders synthesized at 400 °C and 500 °C were 1 and 11 μm, respectively. The band gap values of the obtained powders at 400 and 500 °C was determined by UV–vis spectroscopy as 2.26 eV and 2.24 eV, respectively. The photoelectrochemical analysis of the SnS2 photoelectrode produced at 500 °C revealed a flat band potential of −0.50 V, a charge carrier density of 1.49 × 1020 cm −3 and photocurrent density of 2.5 μA/cm2 at 0 V vs SCE. These results indicated that SnS2 synthesized for the first time by the thermal sulfurization technique from SnO2, which was a simple and cheap technique, was a promising candidate to be used as a photocatalysts.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Fizik; Yoğun Madde 1:Yapısal, Mekanik ve Termal Özellikler; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Physics; Condensed Matter 1: Structural, Mechanical and Thermal Properties; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; ENERJİ VE YAKITLAR; FİZİK, YOĞUN MADDE; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; PHYSICS; ENERGY & FUELS; PHYSICS, CONDENSED MATTER; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Yakıt Teknolojisi; Yoğun Madde Fiziği; Enerji Mühendisliği ve Güç Teknolojisi; Renewable Energy, Sustainability and the Environment; Physical Sciences; Fuel Technology; Condensed Matter Physics; Energy Engineering and Power Technology; Hydrogen production; Photocatalyst; Solar energy; Thermal sulfurization; Tin disulfide; Water splitting; Tin disulfide; Photocatalyst; Solar energy; Water splitting; Hydrogen production; Thermal sulfurization